2018
DOI: 10.1007/s00276-018-2054-9
|View full text |Cite
|
Sign up to set email alerts
|

Localization of orbit in patients with maxillary sinus hypoplasia: a radiological study

Abstract: The orbit has a medial localization in patients with maxillary sinus hypoplasia resulting in a higher complication risk during endoscopic sinus surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Unless recognized, this could result in inadvertent perforation of the orbit whilst performing an ethmoidectomy during endoscopic sinus surgery (ESS) for a chronically obstructed and hypoplastic MS. 25 Craniofacial syndromes resulting in midface hypoplasia result in developmentally small maxillary sinuses. This will be bilateral in conditions such as Crouzon's and Apert's syndrome and following cleft palate repair; unilateral hypoplasia is seen in Hemifacial Microsomia (Pruzansky Grade 1) 26 , 27,28 Chronic inflammation of the sinonasal mucosa during childhood can result in impaired growth of the paranasal sinuses. The volume of the maxillary sinuses decreased and the bony thickness of the sinus walls increased with longstanding paediatric chronic rhinosinusitis.…”
Section: Abnormal Developmentmentioning
confidence: 99%
“…Unless recognized, this could result in inadvertent perforation of the orbit whilst performing an ethmoidectomy during endoscopic sinus surgery (ESS) for a chronically obstructed and hypoplastic MS. 25 Craniofacial syndromes resulting in midface hypoplasia result in developmentally small maxillary sinuses. This will be bilateral in conditions such as Crouzon's and Apert's syndrome and following cleft palate repair; unilateral hypoplasia is seen in Hemifacial Microsomia (Pruzansky Grade 1) 26 , 27,28 Chronic inflammation of the sinonasal mucosa during childhood can result in impaired growth of the paranasal sinuses. The volume of the maxillary sinuses decreased and the bony thickness of the sinus walls increased with longstanding paediatric chronic rhinosinusitis.…”
Section: Abnormal Developmentmentioning
confidence: 99%
“…In previous literature, patients with a hypoplastic MS were reported to have a higher presence of FS hypoplasia . In addition, medial displacement of orbit in patients with MS hypoplasia was evident in the report by Ozcan et al In these recent studies, the touchstone of the method was evaluation of the structures upon paranasal CT scans because paranasal CT was suggested to be the gold standard technique for evaluation of paranasal sinuses . The association between FS pneumatization and olfactory fossa was at the center of several prior studies, but we also focused on olfactory fossa depth and lateral lamella length in patients with MS and SS hypoplasia.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, we found that patients with MS hypoplasia (particularly type 3 hypoplasia) had a deeper olfactory fossa and longer lateral lamella, as did patients with SS hypoplasia. Thus, patients with MS hypoplasia might be under a higher risk of skull base injury as well as lamina papyracea injury . Nevertheless, the limited number of patients with type 3 MS hypoplasia (only 13) could be considered a limitation of our study.…”
Section: Discussionmentioning
confidence: 95%
“…According to Bolger’s classification system, it is a bilateral type I MSH, with morphologically unaltered uncinate process and ethmoidal infundibulum, as documented in CBCT. Various studies have used Bolger’s classification of MSH [ 2 , 3 , 4 , 8 , 10 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Numerous studies have documented MSH mostly, or exclusively, by coronal CT slices [ 2 , 6 , 8 , 17 , 18 , 19 , 22 , 23 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selçuk et al (2008) added several other possible modifications in MSH: bony thickening of sinus wall, hypoplasia or aplasia of other sinuses, canine fossa elevation, anterior ethmoidal cell variation, and presence of ethmomaxillary sinus [ 8 , 9 ]. Cases of MSH have also been detected with superior orbital fissure asymmetry [ 5 ] or enlargement [ 9 ], medial localization of the orbit [ 10 ], depression of the orbital roof [ 11 ], and lateral displacement of the infraorbital canal [ 9 ]. Posterior ethmoid air cells expanded within the MS are regarded as ethmomaxillary sinuses [ 12 ].…”
Section: Introductionmentioning
confidence: 99%